Comparison of Linear and Phased Array Transducers in Ultrasonographic Diagnosis of Pneumonia in Dogs - Mohandas,; Unny, Madhavan; Yesudas, Ajith; George, Arun; Philip, Laiju M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The aim of this study was to evaluate the use of linear and phased array transducers in the ultrasonographic diagnosis of pneumonia  in dogs. Eleven dogs with radiographic signs suggestive of pneumonia formed the population under the study. Radiographic findings  recorded in the study included alveolar pattern, bronchial pattern, lobar sign and unstructured interstitial pattern primarily distributed  in the cranioventral thoracic region. Lung ultrasonography was performed as per Vet-BLUE protocol in nine acoustic windows. The  prominent sonographic features observed were the B-lines, thick and irregular pleura, shred sign with air bronchogram and tissue  signs. Linear transducers were able to detect these findings more extensively than phased array transducers. On B-line scoring, strong  positive sites were found in the cranial and middle lung regions in 86.36% and 81.81% of sites, respectively, with the linear transducer and  36.36% and 54.54% of sites, respectively, using the phased array transducer. Higher numbers of total strong positive sites were detected  with the linear transducer in 56.81% of the total sites. Shred signs, irregular pleura and tissue signs were also recorded and evaluated.  The study suggested that linear transducers were superior in diagnosing superficial lung abnormalities associated with pneumonia.
Keywords: B-line scoring; Dogs; Lung ultrasonography; Pneumonia